The role of stem cells in obstetrics and gynecology: A systematic review - Mirani, Putri; Legiran; Kesty, Cindy; Andrina, Hana (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Stem cell technology has various roles in the field of obstetrics and gynecology, including fertility study as well as tissue damage repair. Safety profile of stem cells technology use in human still need to be assessed.   ABSTRACT Objective: This study aimed to review the role of stem cells in obstetrics and gynecology. Materials and Methods: This review used several databases, the PubMed, Wiley Online Library, and ScienceDirect to search open access original and review articles in English related to stem cells, obstetrics, and gynecology in the last 10 years. The results were analyzed qualitatively. Results: Out of 1,016 records identified through database searching, fifteen articles were eligible for review. Several articles reported the role of stem cells in endometrium repair. Stem cell can also increase endometrial thickness and increase the likelihood of pregnancy. In the field of gynecology, stem cells can be used as potential treatment for stress urinary incontinence and anal incontinence. Despite of all those abilities, stem cells might have errors, such as chromosomal abnormalities, epigenetic and genetic defect, which could potentially turn the stem cells into tumor initiating cells (TICs), thus can contribute to ectopic growth of endometrium (endometriosis), leiomyoma, leiomyosarcomas, and adeno-myosis. Conclusion: Stem cell technology has various roles in the field of obstetrics and gynecology, including fertility study as well as tissue damage repair. However, in-depth research to ensure the safety profile of stem cells technology use in human is necessary.